1991
DOI: 10.1063/1.106157
|View full text |Cite
|
Sign up to set email alerts
|

375-GHz-bandwidth photoconductive detector

Abstract: We report the development of a new, integrable photoconductive detector, based on low-temperature-grown GaAs, that has a response time of 1.2 ps and a 3-dB bandwidth of 375 GHz. The responsivity is 0.1 A/W. Signal amplitudes up to 6 V can be produced with virtually no degradation in response time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(42 citation statements)
references
References 11 publications
2
40
0
Order By: Relevance
“…9 The use of new light absorbing materials and improved fabrication methods has resulted in photodetectors with electrical bandwidths approaching 1 THz. [10][11][12] Devices with 60 GHz bandwidths and high quantum efficiencies at visible and near infrared wavelengths ͑400-1700 nm͒ are now available commercially. 13,14 Of equal importance, since these detectors contain little or no built-in amplification, has been the development of solid state microwave ͑1-90 GHz͒ amplifiers with excess noise comparable to or less than room temperature thermal noise.…”
Section: Introductionmentioning
confidence: 99%
“…9 The use of new light absorbing materials and improved fabrication methods has resulted in photodetectors with electrical bandwidths approaching 1 THz. [10][11][12] Devices with 60 GHz bandwidths and high quantum efficiencies at visible and near infrared wavelengths ͑400-1700 nm͒ are now available commercially. 13,14 Of equal importance, since these detectors contain little or no built-in amplification, has been the development of solid state microwave ͑1-90 GHz͒ amplifiers with excess noise comparable to or less than room temperature thermal noise.…”
Section: Introductionmentioning
confidence: 99%
“…As with the simple detector gaps, it is defined between two coplanar metal lines. With an incident optical energy of 0.04 pJ pulse-~, this LT-GaAs detector has demonstrated a 3 dB bandwidth of 375 GHz with a responsivity of 0.1 A W-~, making it the fastest high-sensitivity detector reported [29]. The dark current at a 1 V bias is 100 pA, and for a higher optical fluence of 22 pJ pulse-~ the on-state resistance of the detector is as low as 30 ~2…”
Section: Lt-gaas Photodetectors and Photoswitchesmentioning
confidence: 89%
“…This contains both terahertz (ac) and Joule heating (dc) components (7) The mean power of the terahertz component may be found by disregarding the constant offset and averaging the sinusoidal terms, to give an expression consistent with that derived by Brown et al [15] (8) The Joule heating may be found by solving (2) for the steady state solution (using a constant, time averaged value of ). Thus the energy dissipated in the photoconductor resistance is given by (9) In practice, the applied bias is governed by the current threshold at which the power dissipated as heat in (9) causes damage to the device. Thus, back substituting from (9) for the bias in (8) gives the maximum emitted terahertz power at the dc power limit for the photoconductor.…”
Section: Photomixing Mechanismmentioning
confidence: 99%